2022
DOI: 10.3390/su14137731
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Neighbors: The Spatial Spillover Effect of Crisis Learning on Local Government

Abstract: Accident prevention is an important prerequisite for achieving sustainable development, and effective crisis learning is a necessary path to it. This article focuses on whether local governments in non-accident areas learn from crises in accident areas, that is “learn from the mistakes of neighbors” and “grow in wisdom.” Using panel data from 2006–2017 for 30 provinces in China, our empirical test discovered that there is not a one-to-one relationship between “learning from neighbors” and “growing in wisdom”; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Unheeded policy spillovers may exaggerate or understate the effects of a certain policy (Angelucci & Maro, 2015; Baird et al, 2015). Evidence from China demonstrated that both political pressure and regulatory pressure induced by major accidents will affect the work safety performance of neighboring provinces, and these are linked via a U ‐shaped nonlinear relationship (Tang & Wang, 2022). At the microlevel, the spillover effect of supervision and inspection activities on enterprises has been found to improve the work safety performance of affiliated enterprises belonging to the same group (Johnson et al, 2017).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unheeded policy spillovers may exaggerate or understate the effects of a certain policy (Angelucci & Maro, 2015; Baird et al, 2015). Evidence from China demonstrated that both political pressure and regulatory pressure induced by major accidents will affect the work safety performance of neighboring provinces, and these are linked via a U ‐shaped nonlinear relationship (Tang & Wang, 2022). At the microlevel, the spillover effect of supervision and inspection activities on enterprises has been found to improve the work safety performance of affiliated enterprises belonging to the same group (Johnson et al, 2017).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Regional safety regulation policies are usually limited to the spatial boundary of specific administrative divisions, but industrial risks may exceed these jurisdictions (Boin, 2019). Spatial spillover effects of industrial accidents and regulatory policies have been reported, but their influence on cross‐administrative cooperation agreements that may amplify these effects have not been fully explored (Shi & Xi, 2018; Tang & Wang, 2022). It is generally assumed that LECA can improve work safety performance by improving local regulation and by sharing resources (Caruson & Macmanus, 2008; Comfort, 2019; Kapucu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…First, according to the "strong porter hypothesis", the stronger the intensity of environmental regulation, the more conducive to curbing agricultural carbon emissions [15]. Moreover, the variation of local government's environmental governance level from bottom competition to definite competition is conductive to produce a significance spatial spillover effect on the environmental governance of adjacent regions [16]. For example, to deal with ecological degradation, the G7 countries have adopted environmental regulations and various measures to reduce carbon emissions [11].…”
Section: The Spatial Spillover Effect Of Environmental Regulation On ...mentioning
confidence: 99%
“…Relevant studies at home and abroad on the spatial spillover relationship between financial support for agriculture and agricultural green development have explored the two aspects. On the one hand, local financial support for agriculture could promote the agglomeration of information, technology and talents in the local region, which is conducive to the information exchange and knowledge spillover of the agricultural environment in the local region, as well as the diffusion of technology and knowledge in adjacent regions, promoting agricultural green development in both local and adjacent regions [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Additionally, with subsidies for delayed fertilization control, soil testing and formula fertilization, and R&D of energy-saving and environmental protection machinery technology, agricultural carbon emissions could be reduced, as well as the adjacent regions due to technology spillovers [22].…”
Section: The Spatial Spillover Effect Of Financial Support For Agricu...mentioning
confidence: 99%
See 1 more Smart Citation